Seismic performance of a retrofitted heritage unreinforced masonry building during the 2010/2011 Canterbury earthquakes. Issue 3 (August 2021) - Misnon, Aina Noor; Abeling, Shannon; Hare, John; Shedde, Devina; Jafarzadeh, Reza; Ingham, Jason; Dizhur, Dmytro
The Heritage Hotel (formerly Old Government Buildings) is one of the architectural heritage icons of Christchurch, New Zealand. Seismic retrofitting was undertaken on the structure in 1995 to achieve the earthquake loading provisions of the 1992 standard for design loadings (NZS 4203:1992). This building is a distinguished 1909 unreinforced masonry Italian High Renaissance palazzo building. The retrofit work included the installation of new lateral load-resisting structural systems, refurbishment of individual building elements, and partial building demolition with a total cost of approximately NZ3.75 million. Detailed observations following the 2010/2011 Canterbury earthquakes showed that the building was subject to only minor damage during the September 2010 earthquake, whereas the February 2011 event caused some damage to exterior stonework and flooding in the basement due to liquefaction. This damage was easily repaired, and the building was fully functional by September 2013. Reported herein are details showcasing the success of the seismic retrofit and post-earthquake performance observations.